Seismic Evaluation of Deficient Reinforced Concrete Weak Beam-Column Joint Frames - Muhammad Rizwan; Naveed Ahmad Akhtar; Naeem Khan; Muhammad Fahad (Archives of Civil Engineering, 2020)
The use of old building design codes and improper execution of recent seismic design practices have caused large amount of substandard and vulnerable reinforced concrete RC building stock majority of which are built with weak beam-column joint connections defect (i.e. joint panel having no transverse reinforcement and built in low strength concrete). In order to understand the seismic response and damage behaviour of recent special moment resisting frame SMRF structures with the defect of weak beam-column joints, shake table tests have been performed on two 1:3 reduced scaled, two story RC frame models. The representative reference code design and weak beam-column joint frame models were subjected to uni-directional dynamic excitations of increasing intensities using the natural record of 1994 Northridge Earthquake. The input scaled excitations were applied from 5% to 130% of the maximum input peak ground acceleration record, to deformed the test models from elastic to inelastic stage and then to fully plastic incipient collapse stage. The weak beam-column frame experienced column flexure cracking, longitudinal bar-slip in beam members and observed with cover concrete spalling and severe damageability of the joint panels upon subjected to multiple dynamic excitations. The deficient frame was only able to resist 40% of the maximum acceleration input as compared to the code design frame which was able to resist about 130%. The seismic performance of considered RC frames was evaluated in terms of seismic response parameters (seismic response modification, overstrength and displacement ductility factors), for critical comparison.